Anesthetic Approach in Ambulatory Vitrectomy: Peribulbar Block vs. Balanced General Anesthesia - Bárbara Gouveia; Leonardo Ferreira; Paula Maia (Anesthesiology Research and Practice)
Background. Vitrectomy is one of the most common outpatient ophthalmic surgeries. The anesthetic technique used in outpatient surgery should contribute to a faster functional recovery, better pain control, and fewer complications. The aim of this study was to compare peribulbar block and balanced general anesthesia, in patients undergoing outpatient vitrectomy. Methods. A prospective cohort study was carried out, including adult patients undergoing ambulatory vitrectomy, between January and February 2018. Peribulbar block or balanced general anesthesia was the independent variable analyzed. Clinical and perioperative variables were evaluated, namely, postoperative pain, nausea, and vomiting in the postoperative period, intraoperative hypotension, patient satisfaction with the anesthetic technique, time to oral diet introduction and to hospital discharge, operating room occupancy time, and pharmacological costs. SPSS® 27 was used for statistical analyses. Results. Twenty-one patients were evaluated, 11 of whom underwent peribulbar block and 10 underwent balanced general anesthesia. Patients undergoing peribulbar block did not experience postoperative pain when compared to patients undergoing balanced general anesthesia (p=0.001). Intraoperative hypotension occurred in 18.2% of patients undergoing peribulbar block and in 70% of those undergoing balanced general anesthesia (p=0.03). Time to oral diet introduction (<1 hour vs. > 2 hours; p<0.05), operating room occupancy time (70 vs. 90 minutes; p=0.027), time to hospital discharge (17 vs. 22.5 hours; p=0.004), and pharmacological costs (4.65 vs. 12.09 euros; p<0.05) were lower in patients undergoing peribulbar block versus balanced general. Conclusions. Peribulbar block seems to meet the criteria of an ideal anesthetic technique in outpatient vitrectomy surgery.